DAMPAK DARI PENGGUNAAN VIDEO DALAM PEMAHAMAN KEMAMPUAN MENDENGAR PADA SISWA TAHUN PERTAMA DI SMAN 1 PEKANBARU - Amalia, Rizki; ', Marzuki; Delfi, Syofia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was an experimental research with one pre-post test design. It was aimed to find out the effect using videos on listening comprehension of the first year students of SMAN 1 Pekanbaru. A single group was invited to be the sample of this study by cluster random sampling to get the treatment. Multiple choice and filling gap test were used both in pre and post-test. The experiment conducted for 5 weeks. Where the first meeting was for the pre-test, the second to seventh meetings were for the treatment and the last meeting was for the post-tes. In order to know the difference between pre and post-test and to analyze the hypotheses, t-test was used. After analyzing the data, it was found out that t-test was higher than t-table which means that alternative hypothesis is accepeted and null hypothesis is rejected. It can be drawn from the result that the students’ score was increasing after given the videos as a treatment. Based on research finding, it is suggested that teachers use video in teaching listening and students watch more videos outside the classroom to comprehend the language.